Impacto psicológico y adicción a redes sociales durante la pandemia por covid - 19 en estudiantes de secundaria de la Institución Educativa Nacional San Juan de Ayacucho, 2021 - Solano Cardenas, Fiorela Melisa (2022)
Objective: To determine the relationship between psychological impact and addiction to social networks during the COVID-19 pandemic in high school students of the San Juan de Ayacucho National Educational Institution, 2021. Material and method: Quantitative approach study, applied type, prospective, relational level; non-experimental/cross-sectional design; the sample consisted of 110 students, who responded to questionnaires in both characterization variables and an instrument of 21 items for the psychological impact variable, 24 items for addiction to social networks. The results were presented descriptively and Spearman's Rho test was used. Results: 52.7% of the participants were mostly male; with respect to the psychological impact variable, 87.3% did not present and 12.7% did present psychological impact; in the depression symptoms dimension, 59.1% were within the normal range, 30.9% mild and 10.0% moderate; in the anxiety symptoms dimension, 49.1% presented a mild level, 38.1% normal and 11.8% moderate; in the stress symptoms dimension, 55.4% were within the normal range, 35.4% mild and 7.2% moderate. With respect to the variable addiction to social networks, 48.2% stated almost never, 24.5% sometimes, 21.8% never, 4.5% almost always and 1.0% stated always. Conclusion: It was determined that there is a moderate and significant relationship between psychological impact and addiction to social networks during the COVID-19 pandemic in secondary school students of the San Juan de Ayacucho National Educational Institution, 2021. Key words: Psychological impact, Covid-19, social network addiction, adolescents.